(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Teaching Russian to Uzbek-speaking university students involves a number of linguistic and pedagogical challenges influenced by differences between the two languages and the multilingual background of learners. This article examines common difficulties in Russian language instruction at the university level, including pronunciation problems, grammatical interference, lexical confusion, and limited speaking confidence. Using a qualitative descriptive approach and classroom-based examples, the study identifies recurring patterns in student performance and discusses practical teaching strategies to address them. The findings suggest that effective instruction requires contrastive explanation, communicative practice and supportive formative feedback. Adapting teaching methods to learners’ linguistic background can significantly improve both language accuracy and communicative competence.